(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents the curriculum of the electronic textbook on the subject "Theory and Methodology of Physical Education". The goals, structure, content and methodological features of the introduction of the electronic format of teaching this subject are revealed. The relevance of introducing digital educational resources into the educational process for students of higher educational institutions of physical education and pedagogy is proven.